(1→3)-β–d-Glucan and Galactomannan for Differentiating Chemical "Black Particles" and Fungal Particles Inside Peritoneal Dialysis Tubing. Issue 4 (July 2016) - Leelahavanichkul, Asada; Pongpirul, Krit; Thongbor, Nisa; Worasilchai, Navaporn; Petphuak, Kwanta; Thongsawang, Bussakorn; Towannang, Piyaporn; Lorvinitnun, Pichet; Sukhontasing, Kanya; Katavetin, Pisut; Praditpornsilpa, Kearkiat; Eiam-Ong, Somchai; et al.
Background: Aseptic, sheet-like foreign bodies observed inside Tenckhoff (TK) catheter lumens (referred to as "black particles") are, on gross morphology, hardly distinguishable from fungal colonization because these contaminants adhere tightly to the catheter. Detection of fungal cell wall components using (1→3)-β–d-glucan (BG) and galactomannan index (GMI) might be an alternative method for differentiating the particles. Methods: Foreign particles retrieved from TK catheters in 19 peritoneal dialysis patients were examined microscopically and cultured for fungi and bacteria. Simultaneously, a Fungitell test (Associates of Cape Cod, Falmouth, MA, USA) and a Platelia Aspergillus ELISA assay (Bio-Rad Laboratories, Marnes-La-Coquette, France) were used to test the spent dialysate for BG and GMI respectively. Results: Of the 19 patients, 9 had aseptic black particles and 10 had fungal particles in their tubing. The fungal particles looked grainy, were tightly bound to the catheter, and appeared more "colorful" than the black particles, which looked sheet-like and could easily be removed by milking the tubing. Compared with effluent from patients having aseptic particles, effluent from patients with fungal particles had significantly higher levels of BG (501 ± 70 pg/mL vs. 46 ± 10 pg/mL) and GMI (10.98 ± 2.17 vs. 0.25 ± 0.05). Most of the fungi that formed colonies inside the catheter lumen were molds not usually found in clinical practice, but likely from water or soil, suggesting environmental contamination. Interestingly, in all 10 patients with fungal colonization, visualization of black particles preceded a peritonitis episode and TK catheter removal by approximately 1–3 weeks; in patients with aseptic particles, a 17-week onset to peritonitis was observed. Conclusions: In all patients with particle-coated peritoneal dialysis tubing, spent dialysate should be screened for BG and GMI. Manipulation of the TK catheter by squeezing, hard flushing, or even brushing to dislodge black particles should be avoided. Replacement of the TK catheter should be suspended until a cause for the particles is determined.